IMPACT OF PROFITABILITY AND PRODUCTIVITY ON THE RISK OF BANKRUPTCY FOR AGRICULTURAL AND FOOD COMPANIES IN VOJVODINA - Tekić, Dragana (Journal of Agricultural Sciences (Belgrade), 2022)
The paper deals with agricultural and food companies which operated on the territory of Vojvodina in 2019. The study analyzed the risk of bankruptcy measured by Altman’s Z-score, as well as profitability and productivity of the observed companies. The aim of the study was to use a multiple regression model to determine the impact of profitability and productivity on the risk of bankruptcy for agricultural and food companies of different sizes (including micro, small, medium and large companies) as well as to compare the results for these two sectors. The comparison of agricultural and food sectors was made according to the size of the companies. The obtained results indicated that profitability has statistically significant positive impact on the risk of bankruptcy for micro and large agricultural companies, while for small agricultural companies the risk of bankruptcy is statistically significantly and positively affected by productivity. The risk of bankruptcy for medium-sized agricultural companies is not affected by the examined indicators. In addition, regression analysis indicated that the risk of bankruptcy for micro and small food companies has statistically significant positive impact on profitability, while for medium and large food companies the risk of bankruptcy is not affected by the observed variables.
Keywords: profitability, productivity, bankruptcy, agriculture, food industry, Vojvodina